Internet en la didáctica de las lenguas extranjeras: un paso adelante - Casanovas Català, Montserrat (Íkala, Revista de Lenguaje y Cultura, 2002)
In the last few years the number of teachers using Technology Enhanced Language Learning (TELL) has increased and numerous articles have been written about the role of technology in foreign language teaching. The most rapidly developing innovations in the area of TELL are happening in relation to the Internet, used not only as a learning tool but also as a real field of language learning with varied, exponentially expanding resources.The purpose of this contribution is to explore the role that the Information and Comunication Technologies (ICT) have and will have in the way foreign languages are taught and learnt. Received: 06-06-02/ Accepted: 28-08-02 How to reference this article: Casanovas Català, M. (2002). Internet en la didáctica de las lenguas extranjeras: un paso adelante. Íkala. 7(1), pp. 53 – 60